2010
DOI: 10.1161/circep.109.899021
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, Mapping, and Catheter Ablation of Recurrent Atrial Tachycardias After Stepwise Ablation of Long-Lasting Persistent Atrial Fibrillation

Abstract: Background-Atrial tachycardias (AT) often occur after ablation of long-lasting persistent AF (CAF) and are difficult to treat conservatively. This study evaluated mechanisms and success rates of conventional mapping and catheter ablation of recurrent ATs occurring late after stepwise ablation of CAF. Methods and Results-A total of 320 patients underwent de novo ablation of CAF using a stepwise ablation approach in 2006 to 2007 at our institution. This study comprised patients who presented with recurrent ATs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
112
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(121 citation statements)
references
References 24 publications
6
112
0
3
Order By: Relevance
“…3 Several studies have shown that termination is predictive for long-term maintenance of SR. [19][20][21][22]33 O'Neill et al reported lower recurrence rates in patients with AF termination during index procedure (5% versus 39%). Termination to SR being associated with the highest single procedure success rate compared with AT or AF at the end of the procedure (42% versus 13% and 25%) was shown by Ammar et al In contrast, Elayi et al noted no impact of termination on SR maintenance.…”
Section: Af Terminationmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Several studies have shown that termination is predictive for long-term maintenance of SR. [19][20][21][22]33 O'Neill et al reported lower recurrence rates in patients with AF termination during index procedure (5% versus 39%). Termination to SR being associated with the highest single procedure success rate compared with AT or AF at the end of the procedure (42% versus 13% and 25%) was shown by Ammar et al In contrast, Elayi et al noted no impact of termination on SR maintenance.…”
Section: Af Terminationmentioning
confidence: 99%
“…Additionally, AT recurrences (often based on macroreentrant mechanisms) can more easily be targeted during repeat procedures and are associated with favorable outcome when compared with CA for AF. 24,33,34 Therefore, occurrence of AT can be considered a step forward to SR.…”
Section: Strategies For Persaf Ablationmentioning
confidence: 99%
“…6,14 In case of macroreentrant ATs, linear ablation was performed, and the end point of bidirectional block was assessed and confirmed by differential pacing maneuvers after restoration of SR. Focal ATs were mapped by assessing the earliest endocardial activation in relation to P-wave onset or, if P-wave onset could not be clearly identified, to a fixed intracardiac electrogram. After AT termination, no attempt at arrhythmia reinduction was performed.…”
Section: Ablation Proceduresmentioning
confidence: 99%
“…[1][2][3][4][5][6] Although arrhythmia recurrences after pulmonary vein (PV) isolation as the sole procedural strategy predominantly consist of AF, subsequent ATs represent approximately half of all recurrences after extensive biatrial substrate ablation. [1][2][3][4][7][8][9] Therefore, a proarrhythmogenic consequence of the ablation procedure itself by creating the basis for zones of slow conduction or enhanced electric automaticity has been proposed to cause these ATs.…”
mentioning
confidence: 99%
“…8,[12][13][14][15] Coffey et al 8 reported a strategy of detailed activation mapping followed by focused entrainment mapping of AF ablation-related ATs. Rostock et al 13 reported that 72% of persistent AF ablation-related ATs are macroreentrant and proposed a mapping strategy starting with entrainment mapping from up to 6 LA sites to establish the correct AT diagnosis. Steven et al 14 proposed a focused mapping strategy based on recognition of a number of biatrial activation patterns.…”
Section: Previous Studiesmentioning
confidence: 99%